1981
DOI: 10.1001/archderm.117.6.349
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bullous disease with coexistent circulating IgG and IgA anti-basement membrane zone antibodies

Abstract: Coexistent circulating IgG and IgA anti-basement membrane zone (BMZ) antibodies were demonstrated in a patient with chronic bullous disease. Direct immunofluorescence microscopy showed IgG, IgA, and C3 deposits in a linear pattern at the BMZ in the patient's uninvolved skin. Ultrastructurally, the bulla was formed beneath the basal lamina as in dermatitis herpetiformis. This investigation might provide evidence for the immunologic overlap of bullous pemphigoid and dermatitis herpetiformis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Miyagawa et al [24] reported a case similar to ours. Their case had circulating IgG and IgA autoantibodies against the basement membrane zone, and the main reactive immunoglobulin was IgG.…”
Section: Discussionsupporting
confidence: 85%
“…Miyagawa et al [24] reported a case similar to ours. Their case had circulating IgG and IgA autoantibodies against the basement membrane zone, and the main reactive immunoglobulin was IgG.…”
Section: Discussionsupporting
confidence: 85%
“…Cases of LABD with IgG antibodies in addition to IgA antibodies deposited in a linear fashion at the BMZ have been reported. 18−23 These cases immunopathologically represent an overlap of LABD and BP. These patients do not meet the strict criteria for the definition of LABD needed for the research setting.…”
Section: Immunopathologymentioning
confidence: 99%
“…При ультраструктурном исследовании уровень полости находился ниже базальной мембраны. Авторами было высказано предполо-жение о существовании группы буллезных дерматозов с перекрестными иммунологическими признаками буллезного пемфигоида и линеарного IgA дерматоза [7].…”
unclassified